DIGITALIZATION OF PESANTREN TRADITION AS DA'WAH RAHMATAN LIL ALAMIN IN THE ERA OF SOCIETY - Ainia Fikri Rahmawati (TASAMUH : Jurnal Komunikasi dan Pengembangan Masyarakat Islam, 2025)
Pesantren as a traditional Islamic educational institution in Indonesia has an important role in shaping the religious values of the community. Along with the development of digital technology and the challenges of the Society 5.0 era, pesantren are required to transform, not only in education management, but also in da'wah strategies. This study aims to describe the form and application of digitalization in pesantren da'wah, analyze the reach and influence of digital da'wah as an expression of rahmatan lil 'alamin, and identify the challenges and opportunities faced in the transformation of da'wah through technology. The approach used is sociological with a descriptive qualitative method, and data is collected through literature studies from scientific journals and verified websites. The results showed that digitalization allows pesantren to deliver da'wah through social media such as YouTube, Instagram, and TikTok with a creative approach that remains based on traditional values. Digital da'wah also expands the reach of pesantren to communities across regions, across ages, and even to the Muslim diaspora. The positive influence is seen in the formation of digital communities that strengthen the narrative of moderate Islam and expand people's understanding of the values of Islam rahmatan lil 'alamin. However, this transformation also presents challenges such as low digital literacy, resistance to internal change, and potential loss of substance if the content prioritizes popular aspects. Therefore, pesantren need to develop digital literacy strategies, strengthen collaboration with technology and media institutions, and maintain a balance between scientific substance and digital content packaging. The digitalization of pesantren traditions, if managed appropriately, can be a strong and inclusive new way of da'wah in the modern era.